Investigating the synthesis of ettringite and monosulfate analogue phases and their use as waste remediation materials - Rae, Rebecca (The University of Edinburgh, 2021)
Pollution from industrial sources into freshwater supplies is a growing global problem with 80 % of all wastewater produced being released into the environment with no treatment. This poses a risk to both human and animal health, as well as affecting the environment and economy. This research will focus on non-organic pollutants, which cannot simply be destroyed and are not biodegradable. The main way these types of wastes are dealt with are by stabilisation and solidification processes where the contaminants are either converted to non-hazardous forms or encapsulated in solid materials to reduce their mobility. The work presented in this thesis will focus on using the mineral ettringite (Ca6[Al(OH)6]2(SO4)3.26H2O) to solidify hazardous waste ions. Ettringite is an important hydration product of Portland cement and also occurs naturally, first being discovered in 1874. It has a well characterised structure crystallising in the space group P31c. The structure consists of cation columns with composition Ca3[Al(OH)6.12H2O]3+, that run parallel to the c axis, with the sulfate anions and remaining water molecules in channels running parallel to these columns. The crystal structure of ettringite has been shown to accommodate other cations, including Fe3+ and Cr3+, on the Al3+ sites, and other oxyanions, including CO3 2- and NO3 - , in place of the SO4 2- in the channels. The ability of the structure to accommodate a range of different ions, gives it the potential for use as a waste remediation material. To test its viability, the synthesis of analogue phases was investigated, along with the time dependence of the formation of these phases. Ettringite analogue phases containing chromate and selenate (Ca6[Al(OH)6]2(XO4)3.26H2O, X=Cr6+, Se6+) were successfully synthesised using the saccharate method. These particular phases were targeted as hexavalent chromium and selenium are hazardous pollutants which affect public freshwater as a result of industrial runoff. With successful syntheses of the chromate and selenate ettringite analogue phases confirmed, a reaction was set up to emulate the remediation process of removing selenium or chromium from solutions, by incorporation into an ettringite analogue phase. The time dependence of the reaction was studied by taking samples at different time points to follow the evolution of the reaction products and removal of the pollutant ions from the solution. Tricalcium aluminate (Ca3Al2O6, C3A) was chosen as the start material and was added to solutions of varying concentrations of chromate or selenate. For chromate containing solutions, the chromate ettringite analogue phase was only formed in concentrated conditions (0.2 M K2CrO4 solution), with weaker solutions (0.01 – 0.1 M K2CrO4 solutions) producing a related phase known as monochromate (Ca4Al2O6(CrO4).xH2O). All tests resulted in the successful removal of hexavalent chromium from solution and solidification of it into the solid phase. For selenate containing solutions, the selenate ettringite analogue phase was formed in all concentrations of solutions (0.02 – 0.2 M Na2SeO4 solutions) when the reaction time was less than 24 hours, with conversion of these phases to the related monoselenate phase (Ca4Al2O6(SeO4).xH2O) at reaction times greater than this. The end result was that selenium was removed from solution and stabilised in a solid phase for all tested concentrations. Solid solution behaviour between the ettringite end member and analogue phase end members was investigated to determine the level of incorporation of the hazardous ions CrO4 2- and SeO4 2- when in the presence of SO4 2-. The chromate-sulfate ettringite series (Ca6[Al(OH)6]2(CrO4)x(SO4)3-x.26H2O) was found to only exhibit solid solution behaviour when x < 0.44, and any attempts to incorporate more chromate resulted in the production of the two end members. The selenate-sulfate ettringite series (Ca6[Al(OH)6]2(SeO4)x(SO4)3-x.26H2O) was found to behave as a complete solid solution for a full range of compositions 0 < x < 3. The solid solution investigation results can inform future remediation strategies if competing sulfur is present in the waste system. Ettringite analogue phases containing iron and gallium (Ca6[X(OH)6]2(SO4)3.26H2O, X=Fe, Ga) were successfully synthesised and the ideal conditions for their formation were investigated. The inclusion of sugar in the synthesis was found to be necessary to produce an ettringite phase with no secondary impurity phases present. The gallium analogue phase could form in 10 minutes, with the iron analogue phase requiring a 24 hour reaction time. The solid solution behaviour between aluminium ettringite and gallium ettringite end members (Ca6[AlxGa1-x(OH)6]2(SO4)3.26H2O, x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0) was investigated and the series was found to form completely. These results demonstrated that gallium could be partially incorporated into the ettringite structure with aluminium also present. From the research presented and discussed in this thesis, the overall conclusions were that the precipitation of ettringite analogue phases and other related materials could be used to remove hazardous ions from water and stabilise them in a solid phase.
Keywords: tricalcium aluminate; ettringite; monosulfate; environmental pollution control; stabilisation and solidification